Selection, characterization and evaluation of streptomyces for the control of anthracnose in chilli / Pedram Shahbazi - Shahbazi, Pedram (2013)

(untitled)
The actinomycetes, mainly Streptomyces spp., have been widely studied as potential biocontrol agents against plant pathogenic fungi. This project was undertaken to isolate and select Streptomyces strains showing potential in vitro and in vivo antifungal activity. Isolation was done from rhizosphere-derived soil of healthy and Colletotrichum-infested chilli plants in Ulu Chechuh in Kuala Selangor and Sungai Burung in the state of Selangor, Malaysia. The selected strains were evaluated for their ability to control chilli anthracnose pathogen, Colletotrichum spp. in vitro, and the best strain among them was chosen for green house experimental trials on chilli in vivo. A total of 130 isolates of actinomycetes were isolated from healthy and Colletotrichum-infested chilli rhizospheric soil on starch-casein, humic acid-vitamin and raffinose-histidine agar. 81.5% of the isolates produced abundant aerial mycelia and were categorized as Streptomyces-like. Twenty-four colonies that lacked aerial mycelia and formed compact orange or brown coloured colonies belonged to the genus Micromonospora. A high proportion (67.9%) of the Streptomyces-like isolates was isolated from the Sungai Burung’s Colletotrichum-infested and healthy rhizospheric soil samples. Moreover, 50% of the Micromonospora-like isolates were obtained from the Sungai Burung’s Colletotrichum-infested rhizospheric soil samples. Four groups of aerial mycelia colour observed in the Streptomyces-like isolates were grey (84.9%), white (8.5%), red (1.9%) and pink (4.7%). 106 Streptomyces-like isolates were assayed for in vitro antagonistic activity against three dominant species of Colletotrichum namely C. acutatum, C. capsici and C. gloeosporioides. The majority of the isolates having pathogen-inhibitory capabilities were from the grey colour group. Twelve isolates inhibited the growth of all test fungi at varying degrees and among them four isolates, P8, P39, P42 and P115, iv showed the best inhibitory action. Isolate P42 was selected for further biocontrol studies because of its strong antifungal activity against all tested Colletotrichum species with the highest degree of antagonism. The antifungal compounds produced by isolate P42 were responsible for 81-94% reduction in mycelial growth of C. acutatum, C. capsici and C. gloeosporioides. Whole cell hydrolysates showed the presence of LL-DAP, classifying selected isolate P42 as a species of Streptomyces. Its aerial spore mass colour was grey with spiral spore chain and smooth-ornamented spores, and the isolate did not produce diffusible pigments. Good growth was observed on ISP2, ISP3, ISP4 and ISP6 agars with optimum growth at pH 7.0 and 28 ± 2°C. It degraded L-tyrosine, xanthine, chitin and starch. Isolate P42 did not require NaCl for growth yet was tolerant to 8% NaCl. It was susceptible to Neomycin, Nanamycin, Novobiocin, Gentamycin, Tetracycline and Streptomycin with inhibition zones ranging from 10-50 mm. It grew well on a variety of carbon sources including D-glucose, galactose, I-inositol, D-xylose, L-arabinose, D-mannitol and rhamnose, but not on sucrose and raffinose. Polyphasic taxonomic studies assigned the isolate under the Streptomyces rochei in the phylogenetic tree. Genotypically it was similar with marker strains S. vinaceusdrappus NRRL 2363T, S. rochei NBRC 12908T, S. plicatus NBRC 13071T and S. enissocaesilis NRRL B-16365T, but differed in some phenotypic characteristics. The strain was designated as Streptomyces rochei. Phytotoxicity effects of isolate P42 were assessed by using low dosage (1.16×105 cfu/ml) and high dosage (1.16×107 cfu/ml) of strain P42 spore suspension on the growth of maize seeds. Isolate P42 in low dosage did not reveal any adverse effect on the seeds and promoted maize seed growth significantly (p<0.05) compared to a high dosage of the isolate. The treatment of the chilli seeds prior to planting and 45 days after planting with 1.16×105 cfu/ml isolate P42 suspension, significantly (p<0.05) reduced the Fruit Symptom Index (FSI) when matured fruits were v challenged with 105 spores/ml of three different Colletotrichum species. Disease Severity Index (DSI) was reduced by 52-54% when plants were treated with low dosage of isolate P42. Isolate P42-treated and untreated control plantlets which were not challenged with Colletotrichum species were healthy.